EFEKTIVITAS LATIHAN ROM DAN BOLA KARET TERHADAP PENINGKATAN KEKUATAN MENGGENGGAM DAN FUNGSI MENGGENGGAM PADA PASIEN STROKE DI RSUD SLEMAN - S Hentu, Ardin; Rochmawati , Erna; Firmawati , Erfin (MEDIA ILMU KESEHATAN, 2018)
Background: Stroke is the third leading cause of death after coronary heart disease and cancer. In stroke patients the main problem that will arise is the damage / death of brain tissue. Signs of the occurrence of damage to brain tissue is paralysis. Range of Motion and Rubber Ball Exercises are Rehabilitation that can be given. This exercise can tone the acupuncture points of the hands that indirectly signal to the sensory part of the nerve to be delivered to the brain. Objective: To know the increase in grasping power and grasping functions in stroke patients after Range of Motion and rubber ball motion exercises. Methods: The design used in this study is experimental quasy, using a control group. This research was conducted in RSUD Sleman. The sample in this study were 26 respondents divided into two groups. Sampling using purposive sample technique. Result : The results of this study indicate an increase in the value of grasping muscle strength and grasping functions in Range of Motion and Rubber ball exercise. Conclusion : Range of Motion exercises and rubber ball movement are effective in improving the value of muscle strength grasping and grasping functions. In expecting further research can increase the number of respondents. Keyword : Grasping Power, Grasping Function, Range of Motion, Rubbing Ball, Stroke.